The Role of the Microbiome in Autism: All That We Know about All That We Don’t Know - Maude M. David (American Society for Microbiology, 2021)
ABSTRACT Autism spectrum disorder (ASD) is a remarkably complex disorder influenced by both genetic and environmental factors. Numerous microbial diversity surveys conducted over the past decade have attempted to link specific ASD biomarkers to gastrointestinal tract disturbances, but results generated across cohorts and studies remain inconsistent. This commentary discusses multidirectional interactions between the host, the microbiome, and external factors germane to autism. Recent studies posit the heritability of the gut microbiome itself, confounding attempts to discern heritable from nonheritable effectors in neurodevelopmental disorders. Elucidating the ever-evolving gut microbiome’s role in modulating the ASD phenotype will most certainly require new experimental methodologies and designs. In a recent paper published in mSystems (J. Fouquier, N. Moreno Huizar, J. Donnelly, C. Glickman, et al., mSystems e00848-20, 2021, https://doi.org/10.1128/mSystems.00848-20), the authors describe a web of interactions by collecting samples longitudinally, analyzing cross-sectional cohorts, and recording nonbinary phenotypic measurements.